KOMUNIKASI DAN SUMBER DAYA DALAM IMPLEMENTASI UNDANG-UNDANG NO 16 TAHUN 2006 TENTANG SISTEM PENYULUHAN PERTANIAN, PERIKANAN DAN KEHUTANAN DI KECAMATAN MELIAU KABUPATEN SANGGAU - Sandy Monaro Negara E.01108101 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Implementation of the Law No. 16 Year 2006 on Extension System for Agriculture, Fisheries and Forestry in District Meliau, indicated less than optimal. This indication is characterized by the lack of intensity counseling is done and the low quality of food crop farmers about modern farming. The purpose of this study was to describe the communication and resources in the implementation of this policy. In this study researchers used a qualitative approach with descriptive research, which describes the facts and phenomena that the researcher have found during the research. the results of this study lead to the communication and resource factors. Communications made between the implementor has gone quite well, but the communication of the implementor to the target policy is still not implemented optimally. Then the resource is divided into three parts, namely financial resources, human and facilities still found some problems, especially for human resources and facilities were minimal in terms of quantity. Conclusions from the research is that the implementation of the law No. 16 of 2006 concerning the extension system of agriculture, fisheries and forestry in the district Meliau there are several obstacles in the communication and resource factors. Finally, for the communication factor, the researcher recommended that the communication to the target policy needs to be optimized, while the recommendation for resource factors that need to be coupled with a good number of extension workers using self-extension and extension of civil servants and cooperating with various parties in the procurement of facilities for tools display extension. Keywords: Communication, Resources, Implementation